Экспериментальные и численные исследования пленочных пьезоэлектрических актуаторов в активных системах виброзащиты пластинчастых элементов машин - Клитной, Владимир Викторович; Кулик, Геннадий Григорьевич (НТУ "ХПИ", 2010)
У статті описані експериментальні та чисельні дослідження використання плівкових п‘єзокерамічних елементів в активних системах віброзахисту пластинчастих елементів машин. Проведений аналіз отриманих результатів АЧХ коливань конструкції при різних умовах навантаження.

An experimental and numerical researches of use film piezoceramic elements in vibro-damping systems lamellar construction unit, was described in the article. The analysis of received results amplitude-frequency characteristic of construction vibrations at the different loading condition was analyzed.
Keywords: конструкционные материалы; распределенные актуаторы; сенсоры; контроллеры; пьезокерамика; численные расчеты